Problematizing Law Enforcement in Indonesia: A Study from the Perspective of the Sociology of Law - Ahmad M; Eka Putri, Afifa; Amin Yasin; Alifandi Rizky Cahya Putra; Arfius Nurdin; Fahri Arfa (Candela Edutech Indonesia, 2025)
Law enforcement in Indonesia faces various complex and multidimensional issues. From the perspective sociology of law, law is not merely seen as a set of formal rules but as part of a social system that reflects the dynamics of society. The main challenges in law enforcement in Indonesia include the gap between normative law and social practices, public distrust in law enforcement officials, and the strong influence of social, political, and economic factors. In this context, the law is often perceived as favoring the powerful while being harsh on the weak, reflecting injustices in its application. This study highlights the importance of judicial system reform, enhancing the integrity of law enforcement officials, and harmonizing state law with prevailing social values in society. The sociological approach to law enforcement in Indonesia emphasizes the need to understand how society perceives, interprets, and complies with the law, as well as how social structures, influence its effectiveness. The gap between formal law and cultural values often results in law legal comoliance. Legal cases highlighted in the media reveal disparities in treatment based on social status. Thefore, the proposed solutions in this study include legal system reform, strengthening legal culture, and active community involvement in legal oversight to achieve a rairer and more effective legal system.